2008
DOI: 10.3168/jds.2007-0434
|View full text |Cite
|
Sign up to set email alerts
|

Limit-Feeding a High-Energy Diet to Meet Energy Requirements in the Dry Period Alters Plasma Metabolite Concentrations but Does Not Affect Intake or Milk Production in Early Lactation

Abstract: Limit-feeding dry cows a high-energy diet may enable adequate energy intake to be sustained as parturition approaches, thus reducing the extent of negative energy balance after parturition. Our objective was to evaluate the effect of dry period feeding strategy on plasma concentrations of hormones and metabolites that reflect energy status. Multiparous Holstein cows (n = 18) were dried off 45 d before expected parturition, paired by expected calving date, parity, and previous lactation milk yield, and randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
27
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 35 publications
(62 reference statements)
8
27
0
1
Order By: Relevance
“…Cows of the L PRE treatment had a relatively higher energy status compared with those of the low energy treatment in the Law et al (2011) study. The greater DMI depression of the H PRE cows of the present study is in agreement with the observations of others Winkelman et al, 2008;Janovick and Drackley, 2010) and supports the hypothesis of Rabelo et al (2003) that the drop in DMI as parturition approaches is greater the higher the energy intake is above requirements during the dry period. Although the energy levels were higher in that experiment, the difference in energy balance between the high and low energy density treatments of Rabelo et al (2003) was comparable to the difference of the current study (23.4 and 27.6 MJ NEL/ day, respectively).…”
Section: Dmi and Energy Status In The Dry Periodsupporting
confidence: 82%
“…Cows of the L PRE treatment had a relatively higher energy status compared with those of the low energy treatment in the Law et al (2011) study. The greater DMI depression of the H PRE cows of the present study is in agreement with the observations of others Winkelman et al, 2008;Janovick and Drackley, 2010) and supports the hypothesis of Rabelo et al (2003) that the drop in DMI as parturition approaches is greater the higher the energy intake is above requirements during the dry period. Although the energy levels were higher in that experiment, the difference in energy balance between the high and low energy density treatments of Rabelo et al (2003) was comparable to the difference of the current study (23.4 and 27.6 MJ NEL/ day, respectively).…”
Section: Dmi and Energy Status In The Dry Periodsupporting
confidence: 82%
“…Other research groups (Rukkwamsuk et al, 1998;Holcomb et al, 2001;Holtenius et al, 2003;Vickers et al, 2013) have reached similar conclusions about controlling energy intake during the dry period, although not all studies have shown benefits (Winkleman et al, 2008). Application of these principles can be through controlled limit-feeding of moderate energy diets or ad libitum feeding of high-bulk, low-energy rations (Janovick and Drackley, 2010;Janovick et al, 2011;Ji et al, 2012) as proposed by others (Beever, 2006).…”
Section: Transition Nutritional Management In Tmr-fed Herdsmentioning
confidence: 78%
“…Similarly Winkelman et al (2008) found no significant effect of a low energy diet in the dry period on calves' weight. Average daily weight gain from birth to 21d of life was significantly higher in the HE group when compared the LE group.…”
Section: Discussionmentioning
confidence: 91%
“…Dry cow nutrition may affect quality of colostrum (Dann et al 2006, Winkelman et al 2008. Colostrum produced by cows and the way of its application to calves during the first day of life are main factors determining the efficiency of colostrum immunoglobulin absorption, and therefore the level of calves' passive anti-infectious immunity (Godden et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation